Vitamin C deficiency reveals developmental differences between neonatal and adult hematopoiesis - Phadke, Ira; Pouzolles, Marie; Machado, Alice; Moraly, Josquin; Gonzalez-Menendez, Pedro; Zimmermann, Valérie S.; Kinet, Sandrina; Levine, Mark; Violet, Pierre-Christian; Taylor, Naomi (Frontiers in Immunology, 2022)
Hematopoiesis, a process that results in the differentiation of all blood lineages, is essential throughout life. The production of 1x1012 blood cells per day, including 200x109 erythrocytes, is highly dependent on nutrient consumption. Notably though, the relative requirements for micronutrients during the perinatal period, a critical developmental window for immune cell and erythrocyte differentiation, have not been extensively studied. More specifically, the impact of the vitamin C/ascorbate micronutrient on perinatal as compared to adult hematopoiesis has been difficult to assess in animal models. Even though humans cannot synthesize ascorbate, due to a pseudogenization of the L-gulono-γ-lactone oxidase (GULO) gene, its generation from glucose is an ancestral mammalian trait. Taking advantage of a Gulo-/- mouse model, we show that ascorbic acid deficiency profoundly impacts perinatal hematopoiesis, resulting in a hypocellular bone marrow (BM) with a significant reduction in hematopoietic stem cells, multipotent progenitors, and hematopoietic progenitors. Furthermore, myeloid progenitors exhibited differential sensitivity to vitamin C levels; common myeloid progenitors and megakaryocyte-erythrocyte progenitors were markedly reduced in Gulo-/- pups following vitamin C depletion in the dams, whereas granulocyte-myeloid progenitors were spared, and their frequency was even augmented. Notably, hematopoietic cell subsets were rescued by vitamin C repletion. Consistent with these data, peripheral myeloid cells were maintained in ascorbate-deficient Gulo-/- pups while other lineage-committed hematopoietic cells were decreased. A reduction in B cell numbers was associated with a significantly reduced humoral immune response in ascorbate-depleted Gulo-/- pups but not adult mice. Erythropoiesis was particularly sensitive to vitamin C deprivation during both the perinatal and adult periods, with ascorbate-deficient Gulo-/- pups as well as adult mice exhibiting compensatory splenic differentiation. Furthermore, in the pathological context of hemolytic anemia, vitamin C-deficient adult Gulo-/- mice were not able to sufficiently increase their erythropoietic activity, resulting in a sustained anemia. Thus, vitamin C plays a pivotal role in the maintenance and differentiation of hematopoietic progenitors during the neonatal period and is required throughout life to sustain erythroid differentiation under stress conditions.